2012
DOI: 10.1177/0093854812436957
|View full text |Cite
|
Sign up to set email alerts
|

Complex Trauma and Aggression in Secure Juvenile Justice Settings

Abstract: Youth in secure juvenile justice settings (e.g., detention, incarceration) often have histories of complex trauma: exposure to traumatic stressors including polyvictimization, life-threatening accidents or disasters, and interpersonal losses. Complex trauma adversely affects early childhood biopsychosocial development and attachment bonding, placing the youth at risk for a range of serious problems (e.g., depression, anxiety, oppositional defiance, risk taking, substance abuse) that may lead to reactive aggres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
211
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(220 citation statements)
references
References 210 publications
8
211
0
1
Order By: Relevance
“…Disempowerment can create a distorted sense of entitlement, and violence can become instrumental in grasping a sense of power and control. Finally, the chaotic household dynamics characterized by family violence may offer few opportunities to observe and experience healthy emotional attachments, paving the way for affective and behavioral dysregulation (Ford, Chapman, Connor, & Cruise, 2012).…”
Section: Implications For Trauma-informed Social Work Practice and Pomentioning
confidence: 99%
“…Disempowerment can create a distorted sense of entitlement, and violence can become instrumental in grasping a sense of power and control. Finally, the chaotic household dynamics characterized by family violence may offer few opportunities to observe and experience healthy emotional attachments, paving the way for affective and behavioral dysregulation (Ford, Chapman, Connor, & Cruise, 2012).…”
Section: Implications For Trauma-informed Social Work Practice and Pomentioning
confidence: 99%
“…Specifically, 35% of detained youth indicated at least one experience of physical assault (Ford, Hawke, & Chapman, 2010). More recent research supports and expands upon the prevalence data to suggest juvenile justice youth have histories of poly-victimization and complex trauma (Ford et al, 2012;Ford, Grasso, Hawke, & Chapman, 2013).…”
mentioning
confidence: 85%
“…histories that are 2 to 3 times higher than youth in the general population (Coleman, 2005;Coleman & Stewart, 2010;Ford, Chapman, Connor, & Cruise, 2012). Two independent studies revealed analogous rates of elevated trauma among detained youth relative to general population youth; approximately 90% of the detained youth reported a history with at least one traumatic event (Abram et al, 2004).…”
mentioning
confidence: 98%
“…In turn, there is a lack of screening and assessment of trauma in secure accommodation (Ford, Chapman, Connor, & Cruise, 2012;Barron & Mitchell, 2017a), little development of trauma-sensitive environments (Hodgdon, Kinniburgh, Gabowitz, Blaustein, & Spinazzola, 2013) and few trauma-specific programmes tailored to the secure accommodation context , all of which are all part of a trauma-informed approach . Over recent years, however, there has been a gradual shift in focus in the US, and Scotland from behavioural interventions to criminogenic understandings and other approaches that seek to address the causes of delinquency to trauma-informed understandings (Marrow, Knudsen, Olafson, & Bucher, 2012;.…”
Section: Punitive/behavioural Approaches and Poor Outcomesmentioning
confidence: 99%